An analysis of the revitalisation of Xitsonga : A dream or Reality - Nkhwashu, Magebula Michael (University of Limpopo ( Turfloop campus), 2010)
This dissertation endeavours to examine the causes of the marginalisation of Xitsonga in South Africa. The study has identified several factors that play a role in the marginalisation of Xitsonga. Some of these factors are inadequate promotion of Xitsonga by State Institutions and the negative attitude that Xitsonga speakers have against their language. In spite of these unfavourable conditions, the study has shown that several measures can be undertaken in order to strengthen Xitsonga as a language. Some of these measures are that Xitsonga must be offered as a subject at school and at tertiary level. Books and newspapers must be written in Xitsonga, to mention but a few. Lastly, the study highlights the fact that the existence of Xitsonga will be determined by its speakers. If they are willing to promote and support it there is no doubt that Xitsonga will exist for a long time to come.
Thesis (M.A. (Translation studies and linguistics)) --University of Limpopo, 2010.
Keywords: language revitalisation; 496.3978; Language, Revival; Tsonga language